Urgensi Pengaturan Presidential Ethics Sebagai Penguatan Sistem Presidensial Dalam Undang-Undang Lembaga Kepresidenan - Aditya Andela Pratama; Kholifatul Muna (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Ethics play an important role in the process of statehood, ethics are also a barrier as well as a constitutional step in strengthening the presidential system. The absence of specific regulations on presidential ethics in Indonesia's positive legal framework will have an impact on the absence of ethical standards in state practice and legal vacuums that have the potential to create ambiguity in the president's standards of behavior in carrying out his functions and authority, both in the formal scope of the state and in broader political interactions. This research aims to examine in depth the importance of presidential ethics regulation and its relationship in strengthening the presidential system of government. The method used is normative juridical with Statute Approach, Conceptual Approach and Philosophical Approach. The results of this study show that the regulation of presidential ethics is very necessary, considering the increasingly complex ethical challenges faced by state leaders in modern political dynamics. The design of the presidential ethics regulation in the Law on Presidential Institutions needs to include three main aspects: ethics in the administration of government, personal ethics of the President, and ethics in public communication. This arrangement is important to ensure that the President exercises power ethically, transparently, and accountably. With clear regulations, it is hoped that it can strengthen the presidential system of government and prevent abuse of power.